석고보드의 첨가제에 따른 오염물질 흡착 및 축열 성능에 대한 고찰 - 서현정(Seo Hyun Jeong); 정수광(Jeong Su-Gwang); 임재한(Lim Jae-Han); 김수민(Kim Sumin) (한국태양에너지학회 논문집, 2015)
Gypsum board is easy to manufacture of a variety of forms and has stable mechanical properties and thermal properties. And gypsum boards are widely used to the walls and ceiling of the building as the interior building materials. The studies about technology of applying the various features in the gypsum board with additives are being actively investigated. Development methods for enhancing performance of the gypsum board using additives are largely divided into two categories. The first case is functional gypsum board that is to improve the moisture absorption and moisture-proof properties. Also studies of adsorption and decomposition of indoor air pollutants of the gypsum board using porous materials as an additive are being actively investigated. Another case is applying thermal storage materials which gives the heat storage performance to gypsum board. In this paper, we would like to introduce the various cases of gypsum board applied various additives.